Avaliação da vitamina D nas gestantes com fetos de peso abaixo do percentil 10 - Marcal, Vivian Macedo Gomes [UNIFESP] (2019)
Objective: To evaluate the vitamin D dosage in pregnant women with small fetuses for gestational age (SGA) and with fetal growth restriction (FGR). Methods: This was a cross-sectional prospective case-control study in which pregnant women with gestational age between 26 and 36 weeks were selected, with fetuses that had adequate weight for gestational age (AGA), small for gestational age (SGA) and fetal growth restriction (FGR), diagnosed by ultrasound. We performed the dosage of Vitamin D, which was evaluated by the chemiluminescence method. In addition, for the numerical variables, the variance analysis model with a fixed factor and Tukey's multiple comparisons method were adjusted; To compare the groups for categorical variables, Fisher's exact test was used. Results: Peripheral blood was collected from 100 pregnant women, and thirteen cases were excluded. No statistical differences were observed between the groups (p=0.672); however, we observed a higher concentration of vitamin D in pregnant women with fetuses affected by FGR compared to the other groups (FGR: 24.80 ng/mL vs. SGA: 23.61). ng/mL vs. AGA: 22.47ng/mL). Conclusion: No statistical difference was found in Vitamin D dosage between fetuses with weight below the 10th percentile.